MODEL KLASTERING SKM3 (SUBCONTROLLED K-MEANS MAX-MIN) DAN APLIKASINYA DALAM MENGHITUNG ELEKTABILITAS PASANGAN CALON KEPALA DAERAH - Tampubolon, Patuan P; Kaloka, Tesdiq Prigel; Swasti, Olivia; Mustika, Widya Fajar; Bustamam, Alhadi (Universitas Sebelas Maret, 2018)
Abstract: Indonesia is a legal state that chooses a leader based on the results of general elections, such as the election of presidents and regional leaders. Electability is statistical data for each pair of candidates who show public interest to choose the candidate. Electability data is usually obtained from the results of questionnaires or interviews with constituents. The data search process is carried out by a survey institution. Most people discuss voluntarily in social media related to the candidate that they will choose. This study uses discussion data from social media to calculate the electability of each pair of candidates by using cluster method. The cluster method is K-Means. K-Means employs euclidean distance to determine the cluster of each data, while the number of cluster can be determined by the user. This study proposes SKM3 model (Subcontrolled K-Means Max-Min), which applies the minimum and maximum average values to decide the cluster of each data. SKM3 cluster is controlled by K-Means method that uses Euclidian distance. SKM3 model is processed using news data from detik.com site for the election of regional leader of West Java, Central Java, and East Java. The error value of SKM3 model is calculated through RMSE (Root Mean Square Error). The error value of West Java is 0.0452, the error value of Central Java up to 0.0343, and the error value of East Java is 0.2382. Based on the error values of each electoral region, it shows that SKM3 model has a small error value, so it can be concluded that SKM3 model is good for calculating the electability of the leader by using clustering method.Keywords:Electability, Clustering, K-Means, SKM3.